2008
DOI: 10.1093/carcin/bgn188
|View full text |Cite
|
Sign up to set email alerts
|

RAGE, carboxylated glycans and S100A8/A9 play essential roles in colitis-associated carcinogenesis

Abstract: Patients with inflammatory bowel diseases are at increased risk for colorectal cancer, but the molecular mechanisms linking inflammation and cancer are not well defined. We earlier showed that carboxylated N-glycans expressed on receptor for advanced glycation end products (RAGE) and other glycoproteins mediate colitis through activation of nuclear factor kappa B (NF-κB). Because NF-κB signaling plays a critical role in the molecular pathogenesis of colitis-associated cancer (CAC), we reasoned that carboxylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
257
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 271 publications
(273 citation statements)
references
References 51 publications
15
257
0
1
Order By: Relevance
“…Stromal S100A8-and S100/A9-positive myeloid cells in a cancer microenvironment have been characterized (Ichikawa et al, 2011;Sheikh et al, 2007;Turovskaya et al, 2008). Previously, we have also observed the enhanced S100A8 and S100A9 expression in infiltrating cells in the stroma of gastric cancers (Choi et al, 2012).…”
Section: A B C D E Fsupporting
confidence: 51%
See 1 more Smart Citation
“…Stromal S100A8-and S100/A9-positive myeloid cells in a cancer microenvironment have been characterized (Ichikawa et al, 2011;Sheikh et al, 2007;Turovskaya et al, 2008). Previously, we have also observed the enhanced S100A8 and S100A9 expression in infiltrating cells in the stroma of gastric cancers (Choi et al, 2012).…”
Section: A B C D E Fsupporting
confidence: 51%
“…Consistent with this, our earlier studies reported that S100A8 and S100A9 were mostly expressed in infiltrating cells in the stroma between gastric tumor cells (Choi et al, 2012). These proteins have been reported to promote cancer proliferation (Turovskaya et al, 2008) and cause cancer metastasis by stimulating the migration of monocytes and tumor cells to metastatic sites (Hiratsuka et al, 2006;2008). Although the role of S100A8/A9 has been reported in smaller studies of gastric cancer cells, the role of stromal S100A8/A9 on migration and invasion of gastric cancer cell has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…N-glycosylation of RAGE further modulates and enhances ligand recognition in two ways. While deglycosylation seems to sensitise RAGE to bind experimental AGE-modified proteins with an extremely high degree of modification by AGE (76-89% lysine residues modified) [20], carboxylated glycans on RAGE increase the affinity for S100-calcium binding protein (S100) and high-mobility group protein 1 (HMGB1) proteins [21,22]. The quaternary structure of the RAGE extracellular domain, but also post-translational modifications of its primary structure, might account for the diversity of ligand recognition.…”
Section: The Multiple Levels Of Regulation Of the Rage Pathwaymentioning
confidence: 99%
“…Carboxylated N-glycans on RAGE facilitate binding of HMGB1 [21] and mediate binding of S100A8/A9 to subpopulation of RAGE on colon cancer cells [22], but increased ligand binding to RAGE can also be observed upon glycation of its ligands [42]. N ( -carboxymethyllysine (CML)-modifications of S100A8 and S100A9 occur in inflammatory bowel disease and enhance RAGE-mediated sustained inflammation [42].…”
Section: The Multiple Levels Of Regulation Of the Rage Pathwaymentioning
confidence: 99%
“…S100A8 appears to have a homeostatic role in pulmonary defense against microbes because S100A8 promotes leukocyte chemotaxis in lungs (Ryckman et al, 2003) and transendothelial as well as transepithelial migration of leukocytes are impaired by inhibition of S100A8 (Raquil et al, 2008;Vogl et al, 2004). Another proposed receptor for S100A8 is glycan-linked RAGE (receptor for advanced glycation endproducts) (Turovskaya et al, 2008). RAGE and TLR4 have been proposed to bind high-mobility group box 1 (HMGB1) that is usually localized in the nucleus but has been reported to be released from cells passively by necrosis during tumor chemotherapy, or actively by lysosomal exocytosis on LPS stimulation in monocytes (Gardella et al, 2002;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%